When Dividends Speak: Corporate Strategy or Market Signal? - Puspitasari, Ratih; Tullah, Dewi Sarifah; Widyaningsih, Aristanti; Haziqah, Ana; Zakaria, Nor Balkish; Febrian, Jan; Supriadi, Yoyon (Jurnal ASET (Akuntansi Riset), 2025)
This study examines the mediating role of dividend policy in the relationship between investment opportunities, leverage, and foreign ownership on market reaction in Indonesia’s energy and basic materials sectors. This research employs multiple linear regression analysis with the Sobel mediation test, using secondary data from 133 publicly listed companies between 2017 and 2023. Data analysis is conducted using EViews 9. The findings show that investment opportunities negatively affect dividend policy, as firms with high growth potential retain earnings. Foreign ownership positively influences dividend policy, suggesting that foreign investors demand higher dividends as a control mechanism. Leverage does not significantly affect dividend policy. Dividend policy positively impacts market reaction, supporting signaling theory, and mediates the effect of investment opportunities and foreign ownership on market reaction but not leverage. These results reinforce corporate life cycle and signaling theories while highlighting that leverage is not a primary determinant of dividend policy. Managers should balance dividend payments with growth strategies, while investors should view dividends as signals of financial stability. This study contributes by incorporating foreign ownership as a determinant of dividend policy and analyzing underexplored sectors in Indonesia.